The Tommyknockers - King, Stephen, 1947-; Smits, Jimmy; Helgenberger, Marg.; Power, John.; Konigsberg Sanitsky Productions, Inc.; K & S II Partnership ([United States] : Lions Gate Home Entertainment, 2005)
A woman in a small New England town stumbles across a strange object buried behind her house and releases a long sleeping ancient evil.
Full screen.
Based on the book by Stephen King.
Originally produced for television broadcast in 1992.
English track: Dolby digital 2.0 surround.
With: interactive menus; scene access; trailer.
Music, Christopher Franke ; editor, Tod Feuerman ; production designer, Bernard Hides ; directors of photography, Danny Burstall, David Eggby ; co-producer, Lawrence D. Cohen ; producers, Jayne Bieber, Jane Scott ; executive producers, Frank Konigsberg, Larry Sanitsky ; teleplay, Lawrence D. Cohen ; director, John Power.
Keywords: Horror films; Television adaptations; Feature films; Films for the hearing impaired